The Protein Protocols Handbook - Walker, John M;Ed (HUMANA PRESS, 2009)
Since the publication of the bestselling second edition of John Walker's widely acclaimed "Protein Protocols Handbook", there have been continual methodological developments in the field of protein chemistry. This greatly enhanced third edition introduces 57 critically important new chapters, as well as significantly updating the previous edition's tried-and-true methods. Although the timely new chapters are spread throughout all of the book, the vital section on post-translational modifications has been expanded most to reflect the increasing importance of these modifications in the. Moins de texte